Lean Seis Sigma: uma análise das contribuições de revistas internacionais sobre essa metodologia - Souza, Wiliam Santos (2016)
Lean Six Sigma (LSS) is a methodology that seeks to increase profitability and business performance through improving processes. Currently, companies who want to keep active and profitable in the market need to search different ways to manage their business in order to make them more agile, increase customer satisfaction and reduce costs. Thus the LSS appears as a viable alternative. Based on this theme, this paper aims to develop a Frame for the contributions of Lean Six Sigma methodology within organizations. The most published works in the area are those who suggest models, frameworks or detailed methods for deployment. Moreover, it has empirical character.